Pest diversity and their environmental drivers on cashew plantations in Guinea-Bissau - Paola Sierra-Baquero; Sílvia Catarino; Gonçalo J. Costa; Zinha Correia; Maria Rosa Ferreira; Elsa Borges da Silva; Maria Cristina Duarte; Maria M. Romeiras; Edgar Varón-Devia; Luís Catarino; Filipa Monteiro (Agriculture, Ecosystems & Environment, 2026)

Understanding acacia dieback: its worldwide distribution and diversity of associated fungal pathogens - Irfana Maqsad; Bárbara Santos; Sofia Conde; Ayman Abdulkareem; Patkó László; Benjamin P.Y-H. Lee; Leili Khalatbari; Filipa Monteiro (South African Journal of Botany, 2026)

Fumonisins’ risk assessment in broa, a maize-based bread – An example from the Portuguese market - Pedro Nabais; Paulo Carmona; Sarogini Monteiro; Helena Sousa; Filipa Melo de Vasconcelos; Duarte Torres; Laura Cunha Silva (Food Control, 2026)

Towards Sustainable Aquafeeds: Valorization of Codium sp. and Osmundea sp. as Functional Ingredients to Enhance Nutrient and Bioactive Compounds in European Seabass - Inês Guerreiro; Filipa Fontinha; Marta Monteiro; Joana Oliveira; Raquel Marçal; Rui Magalhães; Mário Pacheco; Mohamed Soula; Aires Oliva-Teles; Paula Enes; Ana Couto (Journal of Marine Science and Engineering, 2025)
This study aimed to valorize Codium sp. and Osmundea sp. as functional ingredients for European seabass diets. For this purpose, triplicate groups of 25 fish (20.6 g) were fed, during 8 weeks, one of seven diets: the control (CTR), 5% of Codium and Osmundea ground (diets CO and OS, respectively), 5% of Codium and Osmundea ground and autoclaved (diets COA and OSA, respectively), and 0.5% of Codium and Osmundea polysaccharide extracts (diets COP and OSP, respectively). The same diets were used for a digestibility trial. Fish fed the CO diet presented lower growth and an apparent digestibility coefficient (ADC) for dry matter and protein compared to fish fed the CTR and OS diets. Diet COA counteracted these negative effects. No differences were observed in feed intake, feed efficiency, and lipid ADC. Antioxidant enzyme activities and distal intestine histomorphology, an indicator of gut health, were not affected. The expression of interleukin-1β and interleukin-6 increased in fish fed the COP diet. In conclusion, the processing methods counteracted the negative effects of raw Codium, enhancing its value as a dietary ingredient, while its polysaccharides showed immunomodulatory potential that could be valuable during stress or disease periods. These findings support the valorization of these algae for aquafeeds, with Osmundea being safely included at 5% without processing.

Uninvited guests: New stored mangrove rice insect pests in Guinea-Bissau - Sofia Conde; Filipa Monteiro; Sílvia Catarino; Maria Rosa Ferreira; Sónia Ferreira (Journal of Stored Products Research, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Development and characterization of structural connections for modular artificial reefs - Fábio Cruz; Isabel B. Valente; Filipa Monteiro; Dmytro Maslov; Tiago Miranda; Eduardo B. Pereira (Ocean Engineering, 2025)

Comparative study of dietary selenium sources on gilthead seabream (Sparus aurata): Growth, nutrient utilization, stress response and final product quality - Andreia Filipa-Silva; Marta Monteiro; Rafaela S. Costa; Tiago Sá; Alexandra Marques; Luisa M.P. Valente; Claudia Figueiredo-Silva (Aquaculture, 2025)

Emerging Pro-neurogenic Therapeutic Strategies for Neurodegenerative Diseases: A Review of Pre-clinical and Clinical Research - Mariana Vassal; Filipa Martins; Bruno Monteiro; Simone Tambaro; Ricardo Martinez-Murillo; Sandra Rebelo (Molecular Neurobiology, 2025)
The neuroscience community has largely accepted the notion that functional neurons can be generated from neural stem cells in the adult brain, especially in two brain regions: the subventricular zone of the lateral ventricles and the subgranular zone in the dentate gyrus of the hippocampus. However, impaired neurogenesis has been observed in some neurodegenerative diseases, particularly in Alzheimer’s, Parkinson’s, and Huntington’s diseases, and also in Lewy Body dementia. Therefore, restoration of neurogenic function in neurodegenerative diseases emerges as a potential therapeutic strategy to counteract, or at least delay, disease progression. Considering this, the present study summarizes the different neuronal niches, provides a collection of the therapeutic potential of different pro-neurogenic strategies in pre-clinical and clinical research, providing details about their possible modes of action, to guide future research and clinical practice.

Variability and composition of mysid assemblages in a northwest Iberian estuary: Insights from a 10-year data series - Ana Filipa Oliveira; Marta Monteiro; Joana Pereira; Ulisses M. Azeiteiro; Filipe Martinho; Miguel Ângelo Pardal; Sónia Cotrim Marques (Estuarine, Coastal and Shelf Science, 2024)

Cardiorespiratory and muscle oxygenation responses to voluntary hypoventilation at low lung volume in upper body repeated sprints - Cristóvão H. Rosa; Cristina P. Monteiro; Cláudia Barata; Mário C. Espada; Maria João Valamatos; André Bento; Ricardo J. Minhalma; Joana Filipa Reis (European Journal of Applied Physiology, 2024)
Purpose To investigate the impact of voluntary hypoventilation at low lung volumes (VHL) during upper body repeated sprints (RS) on performance, metabolic markers and muscle oxygenation in Brazilian Jiu-Jitsu (BJJ) athletes. Methods Eighteen male well-trained athletes performed two randomized RS sessions, one with normal breathing (RSN) and another with VHL (RS-VHL), on an arm cycle ergometer, consisting of two sets of eight all-out 6-s sprints performed every 30 s. Peak (PPO), mean power output (MPO), and RS percentage decrement score were calculated. Arterial oxygen saturation (SpO 2 ), heart rate (HR), gas exchange, and muscle oxygenation of the long head of the triceps brachii were continuously recorded. Blood lactate concentration ([La]) was measured at the end of each set. Bench press throw peak power (BP PP ) was recorded before and after the RS protocol. Results Although SpO 2 was not different between conditions, PPO and MPO were significantly lower in RS-VHL. $${\dot{\text{V}}}$$ V ˙ E , HR, [La], and RER were lower in RS-VHL, and VO 2 was higher in RS-VLH than in RSN. Muscle oxygenation was not different between conditions nor was its pattern of change across the RS protocol influenced by condition. [La] was lower in RS-VHL than in RSN after both sets. Conclusion Performance was significantly lower in RS-VHL, even though SPO 2 was not consistent with hypoxemia. However, the fatigue index was not significantly affected by VHL, nor was the neuromuscular upper body power after the RS-VHL protocol. Additionally, [La] was lower, and oxygen consumption was higher in RS-VHL, suggesting a higher aerobic contribution in this condition.

Individuals with type 2 diabetes have higher density of small intestinal neurotensin-expressing cells - Filipa P. Ferreira; Sofia S. Pereira; Madalena M. Costa; Marta Guimarães; Nicolai J. Wewer Albrechtsen; Jens J. Holst; Mário Nora; Mariana P. Monteiro (Molecular and Cellular Biochemistry, 2023)
Neurotensin (NT) is a gastro-intestinal hormone involved in several pathways that regulate energy and glucose homeostasis. NT was hypothesized to act in synergy with incretin hormones to potentiate its anti-diabetic effects. Additionally, circulating NT levels were shown to rise after bariatric surgery-induced weight loss. Knowledge of NT-secreting cells distribution along the small intestine and its variation according to diabetes status could provide insights on NT role in mediating type 2 diabetes (T2D) improvement after bariatric surgery. So, our aims were to characterize NT-expressing cell distribution along the human small intestine and to compare the relative density of NT-expressing cells in the small intestine of individuals with and without T2D undergoing bariatric surgery for obesity treatment. Autopsy-derived small intestine fragments ( n = 30) were obtained at every 20 cm along the entire intestinal length. Additionally, jejunum biopsies ( n = 29) were obtained during elective gastric bypass interventions from patients with ( n = 10) or without T2D ( n = 18). NT-expressing cells were identified by immunohistochemistry and quantified via computerized morphometric analysis. NT-expressing cell density increased along the human small intestine. NT-expressing cell density was significantly higher from 200 cm distal to the duodenojejunal flexure onward, as well as in subjects with T2D when compared to those without T2D. NT-expressing cell density increases along the human small gut, and a higher density is found in individuals with T2D. This finding suggests a potential role for NT in the mechanisms of disease and T2D improvement observed after bariatric surgery.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Perception of Citizens Regarding Marine Litter Impacts: Collaborative Methodologies in Island Fishing Communities of Cape Verde - José C. Ferreira; Renato Monteiro; Lia Vasconcelos; Cláudio M. Duarte; Filipa Ferreira; Euclides Santos (Journal of Marine Science and Engineering, 2021)
Marine litter has been considered one of the most serious global challenges, requiring urgent action by governmental bodies, especially in African Small Island Developing States (SIDS), where resources and research are limited. In addition to this, waste management and environmental education and ocean literacy programs in schools are scarce, with islands suffering more seriously from these problems. Despite the amount of literature regarding causes and impacts of marine litter, there is still not enough research conducted concerning the public perceptions on both the problem and the potential solutions. This is even more noticeable in African developing countries, where resources and research are scarce. Perception plays a key role for ecosystem management and conservation policies. This study intends to explore the perceptions of local island fishing communities in Cape Verde regarding marine litter, in order to contribute for an improvement of marine ecosystem management and development of conservation policies. To achieve that, two participatory sessions were conducted in two communities in the island of Santiago—Porto Mosquito and Porto Gouveia—where brainstorming and active listening were used to create shared and authentic spaces for dialogue between the members of the community. Results show that the population of both communities were very aware of the marine litter problem. They were able to identify the lack of a proper waste management system in the island and the inappropriate behaviours of the population as the main causes of this problem. Equipment damages and the presence of plastic inside the fish were the most relevant impacts identified by the participants. These findings reinforce previous research on the importance of public engagement and environmental education to contribute to the conservation of marine ecosystems and to build a strong collaborative ocean governance.

Oak protein profile alterations upon root colonization by an ectomycorrhizal fungus - Mónica Sebastiana; Joana Martins; Andreia Figueiredo; Filipa Monteiro; Jordi Sardans; Josep Peñuelas; Anabela Silva; Peter Roepstorff; Maria Salomé Pais; Ana Varela Coelho (Mycorrhiza, 2017)

Labellum transcriptome reveals alkene biosynthetic genes involved in orchid sexual deception and pollination-induced senescence - Filipa Monteiro; Mónica Sebastiana; Andreia Figueiredo; Lisete Sousa; Helena C. Cotrim; Maria Salomé Pais (Functional & Integrative Genomics, 2012)

Cultivar-specific kinetics of gene induction during downy mildew early infection in grapevine - Andreia Figueiredo; Filipa Monteiro; Ana Margarida Fortes; Martina Bonow-Rex; Eva Zyprian; Lisete Sousa; Maria Salomé Pais (Functional & Integrative Genomics, 2012)

The annual cycle of spermatogenesis in Lipophrys pholis (Blenniidae), a recently proposed sentinel species for pollution monitoring - Filipa Ferreira; Miguel Machado Santos; Maria Armanda Reis-Henriques; Maria Natividade Vieira; Nuno Miguel Monteiro (Ichthyological Research, 2011)

Isolation and characterization of novel polymorphic nuclear microsatellite markers from Ophrys fusca (Orchidaceae) and cross-species amplification - Helena C. Cotrim; Filipa A. Monteiro; Eva S. Sousa; Michael F. Fay; Mark W. Chase; Maria S. Pais (Conservation Genetics, 2009)